2021
DOI: 10.1016/j.jvs.2020.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Combination of mural thrombus and age improves the identification of all-cause mortality following branched endovascular repair

Abstract: Background: In-hospital and 30-day mortality rates of endovascular repair of thoracoabdominal aortic aneurysms shows a significant improvement over open surgery, although we are not seeing a significant difference at 1 year. We assess the hypothesis that a greater mural thrombus ratio within the aorta could function as an indicator of postoperative mortality. Methods:The mural thrombus ratio and preoperative comorbidities of 100 consecutive patients from a single center undergoing endo-debranching between 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The "who and why" of aortic aneurysm mural thrombus is poorly defined. It was thus with great interest that we read the analysis by Patrick et al 7 regarding endovascular repair of TAAA. The concept that patients who have reduced cardiac reserve more readily form mural thrombus as a compensatory mechanism to reduce required stroke volume is quite intuitive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The "who and why" of aortic aneurysm mural thrombus is poorly defined. It was thus with great interest that we read the analysis by Patrick et al 7 regarding endovascular repair of TAAA. The concept that patients who have reduced cardiac reserve more readily form mural thrombus as a compensatory mechanism to reduce required stroke volume is quite intuitive.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of CT scans was performed by individuals who at that time were blinded as to mortality status. With respect to determining a threshold of mural thrombus to create a categorical variable, a cutoff level of 0.5 for inner to outer diameter was utilized because it correlates with the median amount of thrombus amongst our patients and based on the analogous analysis performed by Patrick et al 7 AUC analysis revealed there was no level of inner-to-outer aortic diameter ratio that corresponded to a meaningful sensitivity or specificity with respect to association with 5-year mortality. The area under the curve was 0.509
Figure 1.Examples of measurement of inner and outer AAA diameters.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation